Treatment Patterns for Patients With Unresected Stage III NSCLC: Analysis of the Surveillance, Epidemiology, and End Results (SEER) Database - Shang, Shijie; Wang, Ruiyang; Wang, Fei; Wu, Meng; Chen, Dawei; Yu, Jinming (Frontiers in Oncology, 2022)
Background: Recently, immunotherapy (IO) has shown striking survival improvement in unresectable stage III non-small cell lung cancer (NSCLC). However, the effect of the development on chemo-radiotherapy should not be disregarded. This study aimed to compare the treatment patterns and illustrate the impact of radiotherapy on the cancer-specific survival (CSS) and overall survival (OS) of patients with unresected locally advanced stage III NSCLC. Methods: We retrospectively analyzed the data of patients with stage III NSCLC patients who did not undergo surgery from the National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) database between 2001 and 2016, and three continuous years were regarded as one unit. Using the Kaplan-Meier method, we identified the CSS and OS. Then, a linear regression model was graphed to analyze the correlation between median survival of CSS or OS and calendar years in the radiotherapy alone, chemotherapy alone, and chemoradiotherapy groups. Results: A total of 20986 patients were included in this study. In the overall cohort, CSS and OS improved consistently. To explore the reason for the improved survival, patients were divided into three different cohorts: radiotherapy alone, chemotherapy alone, and chemo-radiotherapy. From 2001 to 2015, the median CSS improved persistently, 7, 8, 8, 9, and 11 months in the radiotherapy alone group and 12, 13, 15, 17, 19 months in the chemoradiotherapy group, but not in the chemotherapy alone group (10, 9, 11, 12, 12 months). To better visualize the correlation between CSS and calendar year, linear regression was performed, yielding r =0.8032, P=0.0395 for the radiotherapy alone group; r = 0.7206, P=0.0689 for the chemotherapy alone group; and r= 0.9878, P=0.0006 for the chemoradiotherapy group. Similar findings were observed in the OS data. Conclusions: The survival of patients with unresectable stage III NSCLC has improved substantially. In addition to IO, radiotherapy played an essential role in the treatment of unresectable stage III NSCLC in the past years and should be considered in the design of clinical trials.